2007
DOI: 10.1159/000098647
|View full text |Cite
|
Sign up to set email alerts
|

Enucleoresection for the Elective Treatment of Small Renal Cell Carcinoma: Can It Be the Treatment of Choice?

Abstract: Background: We present our findings in a series of T1 renal cell carcinomas (RCC) treated with excision of the tumor surrounded by a minimal layer of grossly normal parenchyma. Patients and Methods: A total of 43 patients who underwent elective nephron-sparing surgery performed with enucleoresection were studied retrospectively. None of the patients had preoperative or intraoperative suspicion of positive nodes and were free from distant metastases before surgery (N0, M0). Patients status was last evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The European Association of Urology Clinical Guidelines on renal cell carcinoma (RCC) suggest that nephronsparingsurgeryisanestablishedstandardcurativeapproach forthetreatmentoftumorsupto4cm(andfeasiblefortumorsupto7cm)thatprovidesrecurrence-freeandlong-term survivalratessimilartothoseofpatientssubjectedtoradical nephrectomy [9].Inanexcellenteditorial,Russo [10]underlinedthataccumulatingclinicalevidenceindicatesthatpartial nephrectomy provides equally effective local tumor control asradicalnephrectomydoeswiththeadvantageoflong-term preservation of renal function. In addition, Adamakis et al [11]showedthatenucleoresectionisasafeandacceptableapproach for elective nephron-sparing surgery with outcomes similartothoseofradicalnephrectomy.Theoverzealoususe of radical nephrectomy for small renal tumors must now be consideredsurgicaloverkillaswellasdetrimentaltothelongtermhealthandsafetyofthepatientwithasmallrenalcortical tumor [10].Furthermore,usinganephron-sparingapproach, there is no need for intraoperative frozen section biopsy of the tumor since the kidney is preserved. However, it should behighlightedthatincasesoflargersizetumorsthefollowupshouldbeintensifiedduetoanincreasedriskofintrarenal recurrences [9].Therapeuticapproachesforrecurrenttumors includecompletionnephrectomy,repeatpartialnephrectomy, and more recently ablative techniques such as cryoablation andradiofrequencyablation [12].…”
Section: Discussionmentioning
confidence: 99%
“…The European Association of Urology Clinical Guidelines on renal cell carcinoma (RCC) suggest that nephronsparingsurgeryisanestablishedstandardcurativeapproach forthetreatmentoftumorsupto4cm(andfeasiblefortumorsupto7cm)thatprovidesrecurrence-freeandlong-term survivalratessimilartothoseofpatientssubjectedtoradical nephrectomy [9].Inanexcellenteditorial,Russo [10]underlinedthataccumulatingclinicalevidenceindicatesthatpartial nephrectomy provides equally effective local tumor control asradicalnephrectomydoeswiththeadvantageoflong-term preservation of renal function. In addition, Adamakis et al [11]showedthatenucleoresectionisasafeandacceptableapproach for elective nephron-sparing surgery with outcomes similartothoseofradicalnephrectomy.Theoverzealoususe of radical nephrectomy for small renal tumors must now be consideredsurgicaloverkillaswellasdetrimentaltothelongtermhealthandsafetyofthepatientwithasmallrenalcortical tumor [10].Furthermore,usinganephron-sparingapproach, there is no need for intraoperative frozen section biopsy of the tumor since the kidney is preserved. However, it should behighlightedthatincasesoflargersizetumorsthefollowupshouldbeintensifiedduetoanincreasedriskofintrarenal recurrences [9].Therapeuticapproachesforrecurrenttumors includecompletionnephrectomy,repeatpartialnephrectomy, and more recently ablative techniques such as cryoablation andradiofrequencyablation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of the patients present with metastatic disease, and 20-30% of patients who undergo curative surgery for localised (N0M0) RCC will develop metastatic disease [2][3][4][5]. Only a small number of patients with metastatic disease can be cured by existing therapies.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the results of partial nephrectomies with minimal normal parenchyma around the tumor are not inferior to the studies with widely excised partial nephrectomies found in the literature. Adamakis et al [14] also describe a similar technique on 43 patients, that reproduces the results of partial and radical nephrectomy with minimal morbidity. We have tried to develop the technique even more and apply it to minimal invasive robotic partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%